A degradable triple temperature‐, pH‐, and redox‐responsive drug system for cancer chemotherapy. Issue 12 (22nd September 2018) - Yu, Bing; Song, Na; Hu, Hao; Chen, Guihuan; Shen, Youqing; Cong, Hailin
Abstract: In order to achieve a precise therapeutic effect of cancer treatment and improve the utilization of drugs, a temperature‐, pH‐, and redox‐responsive drug delivery system were synthesized. Methacrylic acid (MAA), poly( N ‐isopropylacrylamide) (PNIPAM), 2‐hydroxyethylmethacrylate (HEMA), and N, N′ ‐ bis (acryloyl)cystamine (BACy), a disulfide bond contained cross‐linker, were polymerized by a distillation‐precipitation polymerization. Doxorubicin (DOX), an anti‐cancer drug, can be loaded into the loose nanoparticle (NP) effectively. The prepared drug delivery remains stable during blood circulation and, when the vectors accumulated at tumor tissues, the pH‐response of MMA and temperature‐response of PNIPAM makes volume shrinkage of vectors which benefit the diffusion of vectors into tumor tissues. After being endocytosed into tumor cell, the disulfide bond that contained in the drug delivery can be cleaved by glutathione (GSH), causing the decomposition of NPs, and then release all of the drug. Under the influence of three trigger factors, the triple stimuli‐responsive drug delivery vectors can realize tumor accumulation, tumor penetration and controlled drug release. Thus, the prepared multi‐responsive NP is ideal drug carriers for developing novel drug delivery systems. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 3203–3210, 2018.